Digital Human Technology in E-Learning: Custom Content Solutions - Sinan Chen; Liuyi Yang; Yue Zhang; Miao Zhang; Yangmei Xie; Zhiyi Zhu; Jialong Li (Applied Sciences)
With advances in digital transformation (DX) in education and digital technologies becoming more deeply integrated into educational settings, global demand for video-based learning materials continues to rise, resulting in substantial effort being required from teachers to create e-learning videos. Furthermore, while many existing services offer visual content, they primarily rely on templates, making it challenging to design custom content that addresses specific needs. In this study, we develop a web service that facilitates e-learning video creation through integrated artificial intelligence (AI) and digital human technology. This service enhances educational content by integrating digital human characters and voice synthesis technologies, aiming to create comprehensive e-learning videos by incorporating visual motion and synchronized audio into educational content. In addition, this service also aims to enable the creation of engaging content through advanced visuals and animations, effectively maintaining learner interest.